Cyclic di-AMP Acts as an Extracellular Signal That Impacts Bacillus subtilis Biofilm Formation and Plant Attachment - Loni Townsley (American Society for Microbiology, 2018)
ABSTRACT There is a growing appreciation for the impact that bacteria have on higher organisms. Plant roots often harbor beneficial microbes, such as the Gram-positive rhizobacterium Bacillus subtilis, that influence their growth and susceptibility to disease. The ability to form surface-attached microbial communities called biofilms is crucial for the ability of B. subtilis to adhere to and protect plant roots. In this study, strains harboring deletions of the B. subtilis genes known to synthesize and degrade the second messenger cyclic di-adenylate monophosphate (c-di-AMP) were examined for their involvement in biofilm formation and plant attachment. We found that intracellular production of c-di-AMP impacts colony biofilm architecture, biofilm gene expression, and plant attachment in B. subtilis. We also show that B. subtilis secretes c-di-AMP and that putative c-di-AMP transporters impact biofilm formation and plant root colonization. Taken together, our data describe a new role for c-di-AMP as a chemical signal that affects important cellular processes in the environmentally and agriculturally important soil bacterium B. subtilis. These results suggest that the “intracellular” signaling molecule c-di-AMP may also play a previously unappreciated role in interbacterial cell-cell communication within plant microbiomes. IMPORTANCE Plants harbor bacterial communities on their roots that can significantly impact their growth and pathogen resistance. In most cases, however, the signals that mediate host-microbe and microbe-microbe interactions within these communities are unknown. A detailed understanding of these interaction mechanisms could facilitate the manipulation of these communities for agricultural or environmental purposes. Bacillus subtilis is a plant-growth-promoting bacterium that adheres to roots by forming biofilms. We therefore began by exploring signals that might impact its biofilm formation. We found that B. subtilis secretes c-di-AMP and that the ability to produce, degrade, or transport cyclic di-adenylate monophosphate (c-di-AMP; a common bacterial second messenger) affects B. subtilis biofilm gene expression and plant attachment. To our knowledge, this is the first demonstration of c-di-AMP impacting a mutualist host-microbe association and suggests that c-di-AMP may function as a previously unappreciated extracellular signal able to mediate interactions within plant microbiomes.